Simulation of Underwater Excavation Using Dredging Procedures - Kouřil, Pavel; Liarokapis, Fotis (My University, 2018)
Underwater excavation is still a very difficult and demanding task. One of the main problems is how to train inexperienced archaeologists. One of archaeologys most challenging tasks is known as dredging. This article presents a novel system for simulating underwater excavation techniques using immersive VR. The focus is not on simulating swimming but on excavating underwater while following established archaeological methods and techniques. In particular, the use of dredging procedures was implemented by a realistic simulation of sand in real-time performance. The working area for performing dredging with an airlift is currently limited to 2 by 2 meters, and users need to excavate it aiming to find artifacts within a specific amount of time.